Female budgerigars prefer males with foraging skills that differ from their own - Yuqi Zou; Zitan Song; Jiani Chen; Yuehua Sun; Michael Griesser (Animal Cognition)
Abstract Foraging skills influence food intake and could therefore also play a role in mate choice decision. Previous empirical work has shown that individuals benefit from being in groups that include individuals with a variety of foraging skills as this increases foraging success. This idea, formalized in the skill-pool hypothesis, may extend to mate choice. Diverse foraging skills can expand the foraging niche of a pair and benefit offspring through enhanced parental provisioning, and exposure to a broader foraging skillset. To test this idea, we trained captive female and male budgerigars to solve one of two different novel foraging puzzle boxes. Then, females simultaneously observed two males that could solve either the same or the other box, and assessed female preferences in a binary mate choice apparatus. Females preferred males with foraging skills that differed from their own, independent of the skill type and the number of times males solved the foraging puzzle. These findings show that foraging skills can influence social preferences, including in a mate choice context, and support intraspecific diversity in foraging skills.